A3.03 Formation of novel citrullinated peptides by porphyromonasgingivalis pad enzyme: Implications for autoimmunity in rheumatoid arthritis. (24th February 2016) - Montgomery, AB; Kopec, J; Shrestha, L; Schewenzer, A; Correia, RE; Fischer, R; Burgess-Brown, N; Yue, WW; Venables, PJ
Abstract : Background and objectives: Peptidylarginine deiminase (PAD) enzymes are thought to be involved in rheumatoid arthritis (RA) due to presence of anti-citrullinated protein antibodies (ACPA). Periodontitis is a risk factor for RA, and periodontal pathogen Porphyromonas gingivalis has been proposed as the link due to expression of the unique prokaryotic PAD enzyme PPAD. PPAD has specificity for C-terminal arginine substrates, resulting in formation of citrullinated epitopes distinct from those formed by mammalian PADs, which could induce a citrulline specific response. By solving the 3D crystal structures of wild-type (wtPPAD) and inactive mutant PPAD (mutPPAD) we aimed to determine mechanisms for the unique activity of PPAD, and compare function to human PAD2 and PAD4 in vitro. Materials and methods: Recombinant PAD2, PAD4 and wt-/mutPPAD were expressed and purified from E.coli. wt-/mutPPAD was crystallised with bound arginine ligands and the 3D structure solved using molecular replacement. In vitro, PPAD/PAD activity was measured using a colourimetric assay for detection of citrulline from synthetic peptides. PPAD/PAD specificity was then quantified by mass spectrometry of citrullinated peptides formed from fibrinogen, following cleavage by proteinase K or P.gingivalis protease arginine gingipain (RgpB). Results: Structural information from wtPPAD and mutPPAD identified the key residues (R152, R154) in determining the C-terminal specificity of PPAD. Mutation of these residues significantly reduced enzyme activity. In vitro, PPAD citrullinates C-terminal arginines only, measured by both colourimetriccitrulline detection and mass spectrometry of citrullinated fibrinogen peptides. PAD2 and PAD4 produced 3 and 2.5 times more citrulline respectively from internal compared to C-terminal arginine residues from synthetic peptides. Sequencing of citrullinated fibrinogen peptides formed by PAD2 and PAD4 also showed higher occurrence of internally citrullinated peptides (65% and 25%), than C-terminal (15% and 4%). Conclusions: PPAD has unique substrate specificity for C-terminal arginine, determined by residues R152 and R154. We have shown the peptides formed by PPAD are not formed readily by human PAD2 or PAD4 and thus would be unlikely to occur in vivo . Following P.gingivalis infection, production of novel citrullinated epitopes could be involved in the breach of tolerance to citrullinated peptides observed in RA.